Willingness to pay for cataract surgeries among patients visiting eye care facilities in Dhaka, Bangladesh - Islam, Muhammed Nazmul; Engels, Thomas; Hossain, Shafayet; Sarker, Malabika; Rabbani, Atonu (Springer Link, 2022)
This article was published in the Applied Health Economics and Health Policy [© Springer Nature Switzerland AG 2019] and the definite version is available at: https://doi.org/10.1007/s40258-019-00478-3 The Journal's website is at: https://link.springer.com/content/pdf/10.1007/s40258-019-00478-3.pdf